(untitled) (Journal of Fatima Jinnah Medical University, 2024)
Background: Suprascapular notch (SSN) is present along the superior border of scapula. Superior transverse scapular ligament converts the notch into an osteo-fibrous foramen. Suprascapular nerve passes below the superior transverse scapular ligament which may undergo calcification resulting in suprascapular nerve entrapment syndrome. This results in shoulder pain with limitation of movement involving muscles supplied by this nerve. The purpose of this study was to analyze the morphology of suprascapular notch in cadaveric scapulae to establish its clinical relevance. Materials and methods: It was an observational study conducted in the cadaveric bone museum of Anatomy Department at Combined Military Hospital, Lahore Medical College and Institute of Dentistry (CMH LMC&IOD). Results: A total of 75 human cadaveric scapulae were observed. Thirty-six scapulae belonged to the right side and 39 to the left side. Overall type-1(28%), type-II (8%), type-III (35%), type-IV (24%), type-V (2.6%) and type-VI (2.6%) were observed. Out of 75 scapulae only 2 (3%) had completely ossified suprascapular ligament and both were on left side. Independent Samples t-test showed statistically significant difference between superior transverse (p-value=0.001), middle transverse (p-value=0.002) and vertical diameters (p-value=0.048) of type-III and type-IV suprascapular notches. Conclusion: This study showed an overall predominance of types III and IV suprascapular notches. This finding is important for surgeons as ossification of suprascapular ligament may predispose patients to nerve entrapment.